Patriarchal inscribed bodies : a feminist theological engagement with body and sexuality in the “Worthy Women Movement” - Stander, Sunelle (Stellenbosch : Stellenbosch University, 2016)
Thesis (MTh)--Stellenbosch University, 2016.